Preventing stunting increase: "Si Penting" program by UPI's community service in Karangwangi village - Darma, Susilo Aditya; Alamsyah, Reksa (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
This community service highlights the severe issue of stunting in Indonesia, notably after the country ranked second in Southeast Asia for the prevalence of toddlers experiencing poor growth in 2018. Stunting has become a primary focus of the Indonesian government. The University of Education Indonesia (UPI), as one of the leading institutions in the country, took the initiative to prevent the increase in stunting rates through the Thematic Real Work Lecture (KKN-T) program with the theme "Si Penting" (Mahasiswa Peduli Stunting). This community service explores the active role of UPI Si Penting KKN-T students in maintaining the Zero Stunting condition in Karangwangi Village. By forming various work programs focused on toddlers, adolescents, and pregnant women, students successfully made positive contributions through activities such as integrated health posts, counseling, awareness campaigns, the CEKAS program, POSBINDU-PTM, the realization of TP-PKK innovations, and the Ketapang Kancana program. The innovative steps taken by TP-PKK and the Karangwangi Village officials create a breakthrough in stunting prevention efforts while simultaneously enhancing the village's self-reliance. Thus, the KKN-T "Si Penting" activities provide a concrete solution for the community in Karangwangi Village and inspire improving health services, especially related to stunting, at the local level.